School Magazines and Possibilities of Their Usage in Media Training - Jirků, Jan (Civilia, 2023)
This text deals with the issue of school magazines and their usage in media training, emphasizing functions that these specific micro-media can fulfill in the educational process at primary and secondary schools in the context of functions that belong to journalism in society in general (according to McQuail's viewpoint). It also accents their possible classification in terms of media typology and integration into the media (eco)system. It deals with the effects of interactivity in the fields of production and perception of school magazines as well.
Keywords: Functionalist Theory of Journalism; Media Education; Media Training; Medium; Micro-medium; School Magazines